Life at court: ideology and audience in the late Assyrian palace - Portuese, Ludovico (marru, 2020)
Intro -- Acknowledgments -- Table of Contents -- List of Tables -- List of Figures -- Conventions -- Abbreviations -- Introduction -- Chapter 1: Sources and Their Reading -- 1.1 The Late Assyrian Empire -- 1.2 Sources and Their Reading -- 1.2.1 Archaeological Sources: the Royal Palace and the City -- 1.2.2 Art Historical Sources: Reliefs -- 1.2.3 Textual Evidence -- 1.3 Kingship and Ideology -- 1.4 Court and Audience -- Chapter 2: Protecting the Palace -- 2.1 Introduction -- 2.2 The Architecture of Two Case Studies -- 2.2.1 Architecture and Connectivity -- 2.3 Doors and Protective Figures -- 2.3.1 Rituals and Incantations -- 2.3.2 Doorways and Circulation -- 2.4 Summary and Further Reflections -- Chapter 3: Reasons for Entering the Palace and Identity of Entrants -- 3.1 Introduction -- 3.2 Great Events -- 3 .2.1 Compulsory Events: Tribute and Audience Gift -- 3.2.2 Procession Scenes -- 3.3 Crime, Arrest, and Public Exhibitions -- 3.4 Private Events -- 3.5 Religious Events -- 3.6 Personal Meetings -- 3.7 Summary and Further Reflections -- Chapter 4: Royal Protocol -- 4.1 Introduction -- 4.2 When Visiting the King -- 4.3 Preparations Before Going to the Palace -- 4.4 In the Palace itself: People Responsible for the Ushering in -- 4.5 Etiquette -- 4.5.1 Insiders -- 4.5.2 Outsiders -- 4.6 The Interpreter -- 4.7 Summary and Further Reflections -- Chapter 5: Before the King -- 5.1 Introduction -- 5.2 Appearing Before the Assyrian King -- 5.3 The King's Appearance -- 5.4 The King's Insignia -- 5.5 The King's Gestures and Etiquette -- 5.7 Summary and Further Reflections -- 5.6 Protection and Assistance for the King -- Chapter 6: During the Stay in the Palace -- 6.1 Introduction -- 6.2 Hospitality -- 6.3 Court Entertainments -- 6.4 Summary and Further Reflections -- Chapter 7: Palace Reliefs -- 7.1 Introduction -- 7.2 Message: Northwest Palace.